Capacitively-coupled measurements on the frequency dependent diagonal magnetoconductance of a 2DEG in GaAs heterostructure in the quantum Hall regime - 이정일; P. J. Stiles; M. Heiblum (ELSEVIER, 1992)
We have examined the complex capacitance of the 2DEG in GaAs heterostructures at a temperature of 1.3 K, magnetic fields up to 8 T and over a range of frequencies from 200 Hz to 100 kHz. The experiment was performed on a high mobility GaAs/AlGaAs heterostructure from an MBE grown wafer with Corbino geometry. We find that the real and imaginary parts of the complex capacitance of the capacitively-coupled structure, are well explained by a one-dimensional diffusion model and the derived diagonal magnetoconductances in the Landau gap regions are in good agreement with those directly measured via a capacitively coupled structure (triple dip method). Spin splitting was also observed at magnetic fields as low as 2.5 T. The value of the enhanced g-factor at high magnetic fields was larger than 2 which is comparable to those determined by conductivity measurements using ohmic contacts. ？ 1992.